2020
DOI: 10.3390/antibiotics9090579
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Carbapenem-Resistant Acinetobacter baumannii Isolated from War-Injured Patients from the Eastern Ukraine

Abstract: Recently, a total of 32 carbapenem- and fluoroquinolone-resistant Acinetobacter baumannii (Ab) isolates was isolated from war-injured patients who were treated at German Bundeswehr Hospitals, and preliminarily typed by “DiversiLab” repetitive elements sequence-based (rep-) PCR. Core genome-based sequence typing was also used to provide more detailed epidemiological information. From the clusters observed by rep-PCR, selected Ab strains were subjected to Next Generation Sequencing (NGS) in order to compare them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 47 publications
(64 reference statements)
1
18
0
Order By: Relevance
“…As an interesting side-effect, cgMLST confirmed the clonal relationships as suggested by rep-PCR in the recent assessment [ 33 ], thus additionally confirming the basic reliability of this comparably cheap and easy-to-perform typing approach for local outbreak scenarios, in spite of the undeniably higher resolution of genome-based typing [ 34 , 40 , 42 ]. A comparison with other A. baumannii isolates from Ukrainian conflict zones that we have investigated did not show any clonality to those in the current study (data not shown) [ 40 ].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…As an interesting side-effect, cgMLST confirmed the clonal relationships as suggested by rep-PCR in the recent assessment [ 33 ], thus additionally confirming the basic reliability of this comparably cheap and easy-to-perform typing approach for local outbreak scenarios, in spite of the undeniably higher resolution of genome-based typing [ 34 , 40 , 42 ]. A comparison with other A. baumannii isolates from Ukrainian conflict zones that we have investigated did not show any clonality to those in the current study (data not shown) [ 40 ].…”
Section: Discussionsupporting
confidence: 53%
“…The latter clustering as observed with the cgMLST-typing confirmed likely transmission events between Syrian patients prior to admission at the Bundeswehr Hospitals Westerstede and Hamburg, which had already been suspected based on the results of rep-PCR and superficial sequencing [ 33 ]. Those transmission events might either have occurred in medical facilities in the patients′ home country but also, as previously discussed for Syrian and Ukrainian war-injured patients treated at German military hospitals [ 33 , 40 , 41 ], during the evacuation flights out of the patients’ crisis-struck home countries. Of note, two strains isolated from Syrian patients at the military hospital in Westerstede (“WEST”-strains) showed completely identical sequences and other isolates of this cluster, which were isolated at the Bundeswehr Hospital Hamburg (“HBG”-strains) showed only one, two, and nine allele differences, respectively ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ST1089 (IC9) strains were the second most common lineage in this study. These strains have been isolated from clinical samples and hospital environments, particularly from studies in Northern Africa and in the Middle East, and are frequently reported to carry blaNDM-1 and blaOXA-94 carbapenem resistance genes (32,(33)(34)(35)(36)(37)(38)(39). An ST1089 strain carrying blaNDM-1 was also isolated from raw milk in a dairy farm in Algeria (40).…”
Section: Discussionmentioning
confidence: 99%
“…Additional screening PCRs [25,26] targeting common beta-lactamases were applied. In addition, whole-genome sequencing from the extracted nucleic acids of the strains was performed as previously described with minor modifications [17,27]. Briefly, sequencing libraries were prepared with the purified DNA using the Ultra II FS DNA Library Prep Kit (New England Biolabs, Frankfurt, Germany) for 250 bp paired-end sequencing runs on an Illumina MiSeq sequencer.…”
Section: Genotypic Assessmentsmentioning
confidence: 99%